2016
DOI: 10.3126/jcmsn.v12i1.14397
|View full text |Cite
|
Sign up to set email alerts
|

Role of transabdominal ultrasound in detection of ectopic pregnancy

Abstract: Background & Objectives: Ectopic pregnancy is one of the common medical emergencies encountered in the clinical practice. Confirmation of diagnosis is usually done by urine pregnancy test and transabdominal sonography. Thus, the present study is carried out to determine the role of transabdominal ultrasonography in the diagnosis of ectopic pregnancy by comparing the ultrasonography findings with that of operative and histopathology and to evaluate clinical profile of the women with confirmed ectopic pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
2
0
0
Order By: Relevance
“…5 Similar age was also found by a study done in Nepal. 7 The overall incidence of ectopic pregnancy in the study period was 0.88% that is 8.8 per 1000 pregnancies and 10 per 1000 deliveries as similar findings in a hospital-based study done in Nepal had found the incidence of 7.3 per 1000 pregnancies and 10.2 per 1000 deliveries. 3 In this study adnexa mass was seen in most of the cases 89 (41.2%) followed by mass with hemoperitoneum 55(25.5%), hemoperitoneum only 43 (19.9%), live ectopic cases 23(10.6%) and gestational sac 4(1.9%) which is similar findings Thapa NB, et al in which adnexal mass with pelvic fluid 15 (83.3%) 7 where as similar other studies stated that hemoperitoneum being the commonest findings during an ultrasound with 95.5% of patients.…”
Section: Table 2 Ultrasoun Features Of Ectopic Pregnancysupporting
confidence: 86%
See 1 more Smart Citation
“…5 Similar age was also found by a study done in Nepal. 7 The overall incidence of ectopic pregnancy in the study period was 0.88% that is 8.8 per 1000 pregnancies and 10 per 1000 deliveries as similar findings in a hospital-based study done in Nepal had found the incidence of 7.3 per 1000 pregnancies and 10.2 per 1000 deliveries. 3 In this study adnexa mass was seen in most of the cases 89 (41.2%) followed by mass with hemoperitoneum 55(25.5%), hemoperitoneum only 43 (19.9%), live ectopic cases 23(10.6%) and gestational sac 4(1.9%) which is similar findings Thapa NB, et al in which adnexal mass with pelvic fluid 15 (83.3%) 7 where as similar other studies stated that hemoperitoneum being the commonest findings during an ultrasound with 95.5% of patients.…”
Section: Table 2 Ultrasoun Features Of Ectopic Pregnancysupporting
confidence: 86%
“…7 The overall incidence of ectopic pregnancy in the study period was 0.88% that is 8.8 per 1000 pregnancies and 10 per 1000 deliveries as similar findings in a hospital-based study done in Nepal had found the incidence of 7.3 per 1000 pregnancies and 10.2 per 1000 deliveries. 3 In this study adnexa mass was seen in most of the cases 89 (41.2%) followed by mass with hemoperitoneum 55(25.5%), hemoperitoneum only 43 (19.9%), live ectopic cases 23(10.6%) and gestational sac 4(1.9%) which is similar findings Thapa NB, et al in which adnexal mass with pelvic fluid 15 (83.3%) 7 where as similar other studies stated that hemoperitoneum being the commonest findings during an ultrasound with 95.5% of patients. 5,11,12 In this study specific findings with live ectopic pregnancy is 10.64% and non-specific findings like adnexal mass, hemoperitoneum and gestational sac being 88.4% which is similar to the study done by Khairy et al in which specific findings of 9.1%.On the other hand, the most common findings by ultrasound were non-specific findings 79.1% and specific findings 19.1% reported.…”
Section: Table 2 Ultrasoun Features Of Ectopic Pregnancysupporting
confidence: 86%